Influence effect of electric action on the micro structure of steel in crystallization - Zhbanova O. M. (Журнал інженерних наук)
The dependence of physical and mechanical properties of manganese steel grade 110H13L on the effect of electrical activity during crystallization of the casting is considered. Treatment of the melt by electric current increases the speed of dissolution of metallic impurities and other components in the melt many times, providing not only finely crystalline structure, but also improving the homogeneity of metal casting. Improvement of mechanical properties is a consequence of crushing those which constitute microstructure. Processing by electric current does a beneficial effect on the process of crystallization of metal melts during casting, which significantly improves the structure of the ingot and its mechanical properties.